Pawon Cerita: Designing a Special Event for a Traditional Culinary Photo Exhibition as a Medium of Cultural Communication at Pasar Papringan - Grace Agatha (Journal of Communication, Sustainability, and Empowerment, 2026)
This practice-based research examines "Pawon Cerita: Saka Dapur, Tumukul Rasa," a visual communication project designed to reframe culinary offerings at Pasar Papringan as cultural narratives rather than mere tourism commodities. The study addresses the strategic challenge of connecting visitors with local kitchen traditions and the core values of "3L" Local (Lokal), Delicious (Lezat), and Sustainable (Lestari) within a community-based tourism context. Theoretically, the project integrates the MOVE framework, the Open-System Model of Event Management, and visual semiotics. Methodologically, it employs a descriptive qualitative approach supported by descriptive quantitative data, utilizing participant observation, documentation, and in-depth interviews with three purposive informant clusters: internal organizers, vendors, and visitors. The project was operationalized through a multi-layered special event consisting of a photography exhibition, walking narrative installations, interactive mirrors, a message corner, and interactive talk shows. Findings reveal that the exhibition reached approximately 4,211 visitors, successfully serving as a "narrative gateway" that guided public interpretation of local food as an expression of village identity and soil-to-table processes. Evaluation data indicated a high level of visitor comprehension regarding 3L values, while qualitative feedback highlighted increased vendor pride and economic benefits. Despite technical constraints in sound systems and digital evaluation reach, the research concludes that Pawon Cerita effectively functions as a medium for cultural communication and identity reinforcement. These results offer strategic insights for enhancing community engagement and narrative design in rural revitalization initiatives.